2021
DOI: 10.1093/neuros/nyab229
|View full text |Cite
|
Sign up to set email alerts
|

Microvascular Decompression for Trigeminal Neuralgia: A Prospective, Multicenter Study

Abstract: BACKGROUND Microvascular decompression (MVD) is the most effective procedure for the long-term management of trigeminal neuralgia (TGN). However, retrospective and single-center studies are inherently biased, and there are currently no prospective, multicenter studies. OBJECTIVE To evaluate the short- and long-term outcomes and complications in patients with TGN who underwent MVD at specialized Japanese institutions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 23 publications
0
25
0
Order By: Relevance
“…Surgical technique is also being improved over time. In a recent prospective cohort study, Mizobuchi and colleagues demonstrated complete pain relief in 80% of patients at three years follow-up, with their higher success rate attributed to transposing the causative vessel away from the trigeminal nerve with a prosthesis, rather than interposing a prosthesis between the vessel and nerve [ 126 ]. The authors in the same study also observed that an arterial compressive pattern better predicted a successful response when compared to patterns of compression due to venous structures or arachnoiditis [ 126 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Surgical technique is also being improved over time. In a recent prospective cohort study, Mizobuchi and colleagues demonstrated complete pain relief in 80% of patients at three years follow-up, with their higher success rate attributed to transposing the causative vessel away from the trigeminal nerve with a prosthesis, rather than interposing a prosthesis between the vessel and nerve [ 126 ]. The authors in the same study also observed that an arterial compressive pattern better predicted a successful response when compared to patterns of compression due to venous structures or arachnoiditis [ 126 ].…”
Section: Treatmentmentioning
confidence: 99%
“… 2 Postsurgical side effects include tinnitus, hearing disturbances, vertigo, facial numbness and palsy, and diplopia. 3 , 4 Additionally, up to 30% of patients report recurrent pain 4 years after MVD surgery for TN. 1 Risk factors for eventual pain recurrence include age younger than 53 years at the time of surgery, symptoms lasting longer than 11.5 years, female sex, and pain on the left side.…”
mentioning
confidence: 99%
“…In general, approximately 16% of patients undergoing MVD for TN will experience symptoms related to cranial nerve (CN) or cerebellar dysfunction. 4 The percentage of patients enduring postsurgical complications is decreased to approximately 5% after 3 years. 4 Such nerve dysfunction is likely due to direct physical interaction with the affected CNs.…”
mentioning
confidence: 99%
See 2 more Smart Citations